The difference in scaling root-planing results between addition of photodynamic therapy and application of metronidazole gel of 25% in chronic periodontitis treatment - Andreas Tjandra; Kwartarini Murdiastuti; Al Sri Koes Soesilowati; Fitri Yuniawati (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Scaling Root-Planing (SRP) is a mechanical treatment for removing hard and soft deposits as well as bacteria that adhere to the tooth surface. The additional use of Photodynamic Therapy (PDT) can lead to damage of pathogen bacteria cell. Metronidazole is a common antibiotic with broad spectrum that goes againsts periodontal pathogen. This study aimed to compare the treatment outcomes between combined treatment SRP+PDT and SRP+metronidazole gel 25% in treating chronic periodontitis from the clinical parameters of Pocket Depth (PD), Relative Attachment Level (RAL), Papillary Bleeding Index (PBI) and the number of bacterial colonies. The study samples were taken from 30 periodontal pocket points, which were divided into two treatment groups. The first group was treated with SRP, then had an application of chlorophyll into the pockets and was lighted by 405 nm light, while the second group was treated with SRP, and was applied by metronidazole gel 25% into the pocket. The procedures were started by taking bacteria in the pocket using paper point in two treatment groups, then measuring PD, RAL and PBI as the baseline. After the treatments, PD and RAL results were calculated within observation time of the baseline, the 3rd, the 6th and the 9th weeks, while PBI and the number of bacterial colony were calculated at the baseline and the 3rd week. Distribution of data was analyzed by Shapiro Wilk test and the data reduction used non parametric test of Mann Whitney. The result showed a decreasing level in PD, RAL, PBI and the number of bacterial colony in both groups, but significant difference was seen in PD, and RAL of the baseline of the 9th week. Thus, the study concludes that the combination of SRP+PDT has the same effectiveness when compared to the combination of SRP+metronidazole gel of 25% in chronic periodontitis treatment, and the result is even greater in reducing the level of PD and RAL as seen from the baseline of 9th week measurement.